2011
DOI: 10.5114/aoms.2011.23412
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lymph node status in patients with early gastric carcinoma using double contrast-enhanced ultrasonography

Abstract: IntroductionDouble contrast-enhanced ultrasonography (DCUS) is a new method we used in predicting lymph node metastasis (LNM) in patients with early gastric cancer.Material and methodsSeventy-six patients with early gastric cancer diagnosed by gastroscope and confirmed by pathology after operation were examined using DCUS preoperatively. Group N1 included 15 patients with LNM and group N0 61 patients without LNM.ResultsIn group N1, 13 patients (87%) had marked hyperenhancement during early arterial phase using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Our previous studies [43][46] and other reports [47], [48] have shown that CEUS can be used as an accurate, non-invasive, and reliable diagnostic method for detection and preoperative assessment of advanced gastric cancer. The potential advantages of CEUS are absence of ionizing radiation compared with CT and lower invasiveness than endoscopic ultrasound, which also carries the potential risks of perforation, pancreatitis, bleeding, and infection.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous studies [43][46] and other reports [47], [48] have shown that CEUS can be used as an accurate, non-invasive, and reliable diagnostic method for detection and preoperative assessment of advanced gastric cancer. The potential advantages of CEUS are absence of ionizing radiation compared with CT and lower invasiveness than endoscopic ultrasound, which also carries the potential risks of perforation, pancreatitis, bleeding, and infection.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the sensitivity for diagnosis of lymph node metastasis using oral contrastenhanced sonography is still very low. 18 Similar to other diagnostic modalities, such as endoscopic sonography, computed tomography, and magnetic resonance imaging, evaluation of metastatic lymph nodes by oral contrastenhanced sonography mainly depends on node size as a criterion of malignancy. 34 Nodes smaller than 5 mm in diameter cannot be accurately detected by available imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…14 Previous studies have shown that double contrast-enhanced sonography, in which an oral ultrasound contrast agent is combined with an intravenous contrast agent, is an accurate, noninvasive, and reliable diagnostic method for preoperative assessment and detection of gastric cancer. [15][16][17][18][19][20] Additionally, a strong positive linear correlation (r = 0.921) between the enhanced intensity of primary tumors, a quantitative double contrast-enhanced sonographic measure, and the microvessel density of gastric cancer was revealed by previous study. 21 In this study, the enhanced intensity and clinicopathologic characteristics of patients with gastric cancer were analyzed with the purpose of assessing the enhanced intensity cutoff value for evaluation of the lymph node status and investigating the predictive factors for lymph node metastasis.…”
mentioning
confidence: 99%
“…Therefore, it is important to identify patients with a poor prognosis in order to undertake a more aggressive approach, and perform more careful follow-up to provide early surgery of the relapse. There is a need to look for methods other than histopathology of lymph node metastases detection [ 10 , 11 ]. Nowadays, molecular techniques are developing rapidly.…”
Section: Introductionmentioning
confidence: 99%